2021
DOI: 10.3390/cells10040779
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Gut-Microbial-Inflammasome-Brain Axis in a Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD), a progressive neurodegenerative disorder characterized by memory loss and cognitive decline, is a major cause of death and disability among the older population. Despite decades of scientific research, the underlying etiological triggers are unknown. Recent studies suggested that gut microbiota can influence AD progression; however, potential mechanisms linking the gut microbiota with AD pathogenesis remain obscure. In the present study, we provided a potential mechanistic link betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 85 publications
2
30
0
Order By: Relevance
“…Indeed, analogous alterations are still evident at the overt stage of pathology (15 months of age). Consistently, this study found reduced Firmicutes / Bacteroidetes ratio in the gut of 5xFAD mice at both ages (5 and 15 months) concurrently with increased NLRP3 inflammasome and IL-1β production, which were positively correlated with astrogliosis and microgliosis along with increased cerebral NLRP3 inflammasome and IL-1β [ 109 ].…”
Section: Cognitive Dysfunction and Microbiota In Alzheimer’s Diseasesupporting
confidence: 55%
“…Indeed, analogous alterations are still evident at the overt stage of pathology (15 months of age). Consistently, this study found reduced Firmicutes / Bacteroidetes ratio in the gut of 5xFAD mice at both ages (5 and 15 months) concurrently with increased NLRP3 inflammasome and IL-1β production, which were positively correlated with astrogliosis and microgliosis along with increased cerebral NLRP3 inflammasome and IL-1β [ 109 ].…”
Section: Cognitive Dysfunction and Microbiota In Alzheimer’s Diseasesupporting
confidence: 55%
“…In this study, we assessed the effect of PS128 on the icv-STZ-treated 3 × Tg-AD model and showed that longterm supplementation with PS128 prevented cognitive dysfunction induced by icv-STZ in the 3 × Tg-AD male mice. The beneficial effects of PS128 supplementation on attenuating cognitive deficits were consistent with many other probiotic studies [14,[64][65][66][67]. Therefore, we suggest that PS128 supplementation is safe and has the potential to prevent cognitive dysfunction in individuals with AD.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the in vitro effects of C. phaeocaulis translate into a decrease in IL-1β levels and inflammatory cell infiltration in an animal model of airway inflammation caused by nanoparticles. Considering the fact that NLRP3 inflammasome is mechanistically linked to diverse pathophysiological conditions, including insulin resistance and neuroinflammation [ 17 , 18 ], it will be scientifically worthwhile to evaluate C. phaeocaulis extract in other animal models of diseases associated with excessive activation of NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%